Developing the Competence of Students of Linguistic Higher Educational Institutions to work Independently in Teaching - Amonlikova Nodira Ximmatovna (Genius Publishing Group, 2023)
This article provides a comprehensive overview of the competence of students of linguistic HEIs in teaching, a general understanding of linguistic HEIs, and the importance of their competence to work independently for students
Keywords: teaching process; competence to work independently; -pedagogical activities